Analysis of Marketing Strategies in Overcoming Visitor Decline Gramedia Solo Due to Online Books - Sativa Isach; Wijiastuti, Sri; Darmaningrum, Kurniawati (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze effective marketing strategies in increasing sales at Gramedia Bookstore in Solo City amid the increasing popularity of e-commerce platforms and ease of access to online book purchases which have changed consumer behavior and resulted in a decrease in visits to physical bookstores. Methodology: This study uses a quantitative method by collecting data through a questionnaire distributed to 100 respondents who are or have visited the Gramedia Slamet Riyadi Solo Bookstore. Data analysis was performed using multiple linear regression with the help of SPSS software version 30. Main Findings: Brand Experience, store atmosphere, and service quality have a significant effect on revisit intention to Gramedia Bookstore in Solo City. Brand Experience has a t-value of 2.141 (sig. 0.035), store atmosphere of 3.879 (sig. <0.001), and service quality of 2.308 (sig. 0.023). Simultaneously, this variable had a significant effect with an F value of 19.569 (sig. <0.001) and an Adjusted R² of 0.360. Novelty/Originality of this study: This study provides insight into the importance of strategies based on brand experience, store atmosphere, and service quality in increasing customer revisit intent to physical bookstores in the digital era. These findings can serve as a reference for the book retail industry in facing the challenges of competition with e-commerce platforms.